Study on optimal mathematical model to eradicate Ebola. (2016) - Yuan, Shujuan; Zhang, Yi; Liu, Yalou; Han, Xiuli
Having been raging the West African land for almost one year, Ebola virus causes a global panic because of its terrible high-speed infection and high mortality rate. To meet the drug supply chain and transport chain requirements, three models are established to help reduce the increasing number of patients. First, we constructed the fitting model of the number of patients according to the principle of least squares. Second, based on the theory of joint managed inventory, the optimal route in the supply chain and optimal cost model are constructed. Then, according to the characteristics of the inflection of Ebola virus, dynamic model is established. In drug flow system, by applying the supply chain model to constrain the drug in different ways, the optimal allocation plan is achieved. In inter city transportation, by using the ant colony algorithm, the optimal path can be found in the same region.